Evaluating the domains of generalism and equity, diversity and inclusion in preclinical simulated cases for targeted curricular improvements - Thomas Soroski; Kuda Hove; Lisa Steblecki; Jaime C. Yu (Medical Education Online)
Background Simulated cases are widely used in medical education to develop clinical reasoning skills and discuss key topics around patient care. Such cases present an opportunity to demonstrate real world encounters with diverse patient and health provider identities, impacts of social and structural determinants of health, and demonstrate a generalist approach to problems. However, despite many calls-to-action for medical schools to better incorporate equity, diversity and inclusion (EDI) and generalism, it remains difficult to evaluate how well these goals are being met.Methods A quality improvement project was completed at a single medical school to evaluate the domains of generalism and EDI within simulated cases used in the preclinical curriculum. Generalism was evaluated using the Toronto Generalism Assessment Tool (T-GAT). EDI was evaluated using a locally developed novel tool. Analysis included descriptive statistics and Pearson correlation coefficient.Results A total of 49 simulated cases were reviewed. Twelve generalism and 5 EDI items were scored on a 5-point Likert scale, with higher scores indicating better demonstration of generalism or EDI within a case. Average generalism score across all cases was 45.6/60. Average EDI score across all cases was 11.7/25. Only 21/49 cases included representation of one or more diverse identity categories. The most common diverse identity represented was non-white races/ethnicities, and the identity represented the least was diversity in language fluency. Generalism and EDI scores demonstrated a weak positive correlation (R2 = 0.25).Conclusions Quantitative evaluation of simulated cases using specific generalism and EDI scoring tools was successful in generating insight into areas of improvement for teaching cases. This approach identified key content areas for case improvement and identities that are currently underrepresented in teaching cases. Similar approaches could be feasibly used by other medical schools to improve generalism and EDI in teaching cases or other curricular materials.